ALIH FUNGSI LAHAN DAN PETANI NENAS DI DESA RIMBO PANJANG KECAMATAN TAMBANG KABUPATEN KAMPAR - Rais Wirawan; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted on the community, especially on pineapple farmers in Rimbo Panjang Village, Tambang District, Kampar Regency. At present the function shift of land in the Village of Rimbo Panjang in the Tambang District of Kampar Regency has already taken place. The theory used is the Theory of Social Change. The method used is a descriptive qualitative approach. The subjects of this study were 6 people, namely the Village Head of Rimbo Panjang, Head of the BPN Office, 2 Pineapple Farmers Owners and Cultivators, 1 Farmer Owner, and 1 Farmer Cultivator. The sampling technique in this study is to use a purposive sampling technique, which is where sampling or withdrawal is done by selecting objects (informants) based on specific criteria set by the researcher. The data source used is the source of data in the form of observation (observation) and interview (interview). Data analysis used in this study is collecting data from various sources by incorporating theories that are used in accordance with social phenomena. The results of this study are that the process of land conversion occurs due to two main factors, namely internal factors and external factors. Internal factors, this factor is more concerned with the side caused by the socio-economic conditions of agricultural land users. Whereas external factors are factors caused by the dynamics of urban growth, demography and economics. The process of land conversion occurs due to landowners being pressured by economic needs, so that landowners sell their land to developers. The existence of land conversion has led to the creation of new jobs or increasingly varied new sectors for pineapple farmers in Rimbo Panjang Village. While the negative impact for pineapple farmers is that if the sale of the land is not utilized as well as possible, it will have a negative impact on the pineapple farmers.Keywords : Land use change, Effect of land use change, pineapple farmer